2005
DOI: 10.1007/bf03217409
|View full text |Cite
|
Sign up to set email alerts
|

Young children’s ability to use the balance strategy to solve for unknowns

Abstract: This article examines students' ability to use the balance model to solve for unknowns. A teaching experiment was conducted in four Year 3 classrooms. This experiment focused on exploring the application of the balance model as an analogue for representing equations and solving for m@,nowns. The teaching experiment promoted a shift by students towards viewing addition and subtraction equations in terms of equivalence, where the situation is viewed in a multi-directional way (i.e., balance). Initially the lesso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 10 publications
3
32
0
3
Order By: Relevance
“…At a general level it is argued that they allow new concepts, entities and operations to become endowed with meaning (Filloy and Rojano, 1989;Da Rocha Falcão, 1995) and can facilitate the link between concrete and abstract thinking Williams, 1996, Brown et al, 1999). However, while concrete models may act as analogues for the intended abstractions (English and Sharry, 1996;Warren and Cooper, 2005), they may mask teachers" intended learning outcomes, necessitating appropriate teacher interventions to ensure appropriate abstraction (Filloy and Sutherland, 1996).…”
Section: Research On Approaches To the Teaching Of Linear Equationsmentioning
confidence: 99%
See 2 more Smart Citations
“…At a general level it is argued that they allow new concepts, entities and operations to become endowed with meaning (Filloy and Rojano, 1989;Da Rocha Falcão, 1995) and can facilitate the link between concrete and abstract thinking Williams, 1996, Brown et al, 1999). However, while concrete models may act as analogues for the intended abstractions (English and Sharry, 1996;Warren and Cooper, 2005), they may mask teachers" intended learning outcomes, necessitating appropriate teacher interventions to ensure appropriate abstraction (Filloy and Sutherland, 1996).…”
Section: Research On Approaches To the Teaching Of Linear Equationsmentioning
confidence: 99%
“…Warren and Cooper (2005), mindful of the inadequacies of the balance with respect to negative quantities, concluded, that it helped "children in approaching problems with unknowns, particularly solving problems with unknowns on both sides of the equal sign" (70). Furthermore, it not only provided a vocabulary with which children could articulate their thinking but also facilitated their seeing the equals sign as representing equivalence rather than an instruction to calculate.…”
Section: Research On Approaches To the Teaching Of Linear Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Systematic attempts to evaluate the balance's efficacy have shown that it helps students to understand the principles of equations, solve non-arithmetical equations with understanding, particularly from the perspective of the need to do the same thing to both sides (Araya et al, 2010;Warren and Cooper, 2005). In addition, it facilitates students' acquisition of an appropriate vocabulary and a relational understanding of the equals sign (Vlassis, 2002).…”
Section: Approaches To the Teaching Of Linear Equationsmentioning
confidence: 99%
“…They persistently interpret it as either a syntactic indicator (i.e., a symbol indicating where the answer should be written) or an operator sign (i.e., a stimulus to action or "to do something") (Behr, Erlwanger & Nicols, 1980;Carpenter, Franke, & Levi, 2003;Saenz-Ludlow & Walgamuth, 1998;Warren & Cooper, 2005). Instead it should be interpreted as quantitative "sameness" (i.e., both sides of an equation are the same and information can be obtained from either direction in a symmetrical fashion) (Kieran & Chalouh, 1992).…”
Section: Teaching Equivalence and Equations In The Ea Tpmentioning
confidence: 99%